2020
DOI: 10.22541/au.159769326.67479490
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Review of Vitamin B12 deficiency in pregnancy -- a diagnosis not to miss as veganism and vegetarianism become more prevalent

Abstract: Vegetarianism and veganism are increasingly popular. However, veganism risks development of vitamin B12 deficiency as it is not available from plant sources. Moreover, its impact may be slow to be detected because body stores of vitamin B12 can last years. There is currently no UK guidance on antenatal diagnosis and management of vitamin B12 deficiency. This paper reviews the metabolism, diagnosis and treatment of vitamin B12 in pregnancy. It concludes that prophylactic vitamin B12 supplementation should be gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…16,17 In this study 68% of the women were non-vegetarians, there was a high prevalence (42.4% with vitamin B12 levels <200mg/dl) of vitamin B12 deficiency among them and 32% were vegetarian of which 51.6% had vitamin B12 deficiency, which is in accordance to the study done by Rashid et al where they found that the pregnant and lactating women on vegetarian and vegan diet were at high risk of deficiency due to increased metabolic demand of vitamin b12. 18 The higher prevalence among the nonvegetarian women can be explained as most of them belong to the low socio-economic strata (67% belonging to lower middle class and below) having low meat consumption.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 In this study 68% of the women were non-vegetarians, there was a high prevalence (42.4% with vitamin B12 levels <200mg/dl) of vitamin B12 deficiency among them and 32% were vegetarian of which 51.6% had vitamin B12 deficiency, which is in accordance to the study done by Rashid et al where they found that the pregnant and lactating women on vegetarian and vegan diet were at high risk of deficiency due to increased metabolic demand of vitamin b12. 18 The higher prevalence among the nonvegetarian women can be explained as most of them belong to the low socio-economic strata (67% belonging to lower middle class and below) having low meat consumption.…”
Section: Discussionmentioning
confidence: 99%
“…No existen en la actualidad guías clínicas respecto al diagnóstico de déficit de vitamina B12 en el embarazo 22 . Existe creciente interés en la inclusión de este déficit vitamínico en los programas nacionales de pesquisa neonatal.…”
Section: Discussionunclassified
“…The increasing popularity of plant-based diets in recent years has been driven by various motives such as perceived health benefits, environmental concerns, and ethical considerations [1,2]. These diets encompass a range of patterns with varying degrees of restriction, including lacto-ovo-vegetarian, ovo-vegetarian, lactovegetarian, and vegan or strict vegetarian diets, which exclude different types of animal products [3].…”
Section: Introductionmentioning
confidence: 99%